Molecular and Digital Biomarker Supported Decision Making in Clinical Studies in Cardiovascular Indications. Issue 6 (23rd April 2016) - Kramer, Frank; Dinh, Wilfried
Abstract : Although a large number of pharmaceutical therapies are available to treat cardiovascular diseases like heart failure, in many medical conditions treatment is still not optimal and, therefore, the need for innovative, safe and efficacious drugs is still very high in this indication. Biomarkers are an important tool in the preclinical and clinical drug development process; they allow patient selection for clinical studies as well as therapy monitoring during studies. Biomarker concepts in cardiovascular indications differ very much from those in oncology and are very diverse. The present article gives an overview of the pathomechanisms of heart failure and describes the socioeconomic impact of the disease and the biomarker strategies being applied in the development of new heart failure drugs. The focus lies on protein biomarkers that can be measured in the blood and on functional biomarkers that can be derived from implanted and wearable medical devices. Abstract : Biomarkers are important tools in the preclinical and clinical drug development process. This review gives an overview of the pathomechanisms of heart failure and the biomarker strategies currently applied in the development of new heart failure drugs, focusing on protein biomarkers that can be measured in the blood and functional biomarkers that can be derived from medical devices.